Short-Term Boron Deprivation Inhibits Endocytosis of Cell Wall Pectins in Meristematic Cells of Maize and Wheat Root Apices - Yu, Qin (American Society of Plant Physiologists, 2002)
By using immunofluorescence microscopy, we observed rapidly altered distribution patterns of cell wall pectins in meristematic cells of maize (Zea mays) and wheat (Triticum aestivum) root apices. This response was shown for homogalacturonan pectins characterized by a low level (up to 40%) of methylesterification and for rhamnogalacturonan II pectins cross-linked by a borate diol diester. Under boron deprivation, abundance of these pectins rapidly increased in cell walls, whereas their internalization was inhibited, as evidenced by a reduced and even blocked accumulation of these cell wall pectins within brefeldin A-induced compartments. In contrast, root cells of species sensitive to the boron deprivation, like zucchini (Cucurbita pepo) and alfalfa (Medicago sativa), do not internalize cell wall pectins into brefeldin A compartments and do not show accumulation of pectins in their cell walls under boron deprivation. For maize and wheat root apices, we favor an apoplastic target for the primary action of boron deprivation, which signals deeper into the cell via endocytosis-mediated pectin signaling along putative cell wall-plasma membrane-cytoskeleton continuum.